Evaluation of Isolated Compounds from Wood of Artocarpus heterophyllus as A Cosmetic Agent - Enos Tangke Arung; Kuniyoshi Shimizu; Ryuichiro Kondo (Masyarakat Peneliti Kayu Indonesia, 2010)
In our efforts to find new whitening agent materials, we focused on wood of Artocarpus heterophyllus which is anti melanogenesis. By activity-guided fractionation of A. heterophyllus wood extract, norartocarpetin and artocarpesin were isolated which inhibited both mushroom tyrosinase activity and melanin formation in B16 melanoma cells. This compound is a strong candidate as a remedy for hyperpigmentation in human skin that can be used for cosmetic (whitening agent).